Mapping Arabic Discourse: A Substance Analysis and Research Methodology on Master's Thesis Of Arabic Education At State Islamic Universities In Indonesia (PTKIN) - Royani, Ahmad; Ridlo, Ubaid; Umbar, Kisno; Maulidya, Reza Anis (Ijaz Arabi Journal of Arabic Learning, 2024)
This research, of significant importance, aims to investigate the prevailing themes and research methods employed in master's theses in Arabic Language Education in Indonesia from 2011 to 2021. The study also seeks to identify the factors influencing the selection of specific themes and methods. A descriptive qualitative approach is utilized, with the researcher acting as the main instrument for mapping based on a predetermined grid. The primary data for this study consists of 1083 archived theses from Master of Arabic Language Education students at UIN Syarif Hidayatullah Jakarta, UIN Maulana Malik Ibrahim Malang, and UIN Sayyid Ali Rahmatullah Tulungagung, accessible through the e-repositories of each university. The findings, of great significance, indicate that the predominant theme in these master's theses is the study of Arabic teaching materials, accounting for 308 titles or 28.44% of the total. The second central theme is learning design research, with 143 titles (13.20%), followed by Arabic teaching methods with 85 titles (7.85%). Regarding research methods, the research and development (R&D) method dominates the master's theses in Arabic Education, comprising 379 titles (35.05%). Descriptive methods rank second with 319 titles (29.48%), followed by case studies with 190 titles (17.56%). Less commonly used research methods include character studies, which have only six titles (0.55%), and survey methods with three titles (0.28%). The dominance of specific themes and research methods in Arabic education indicates a preference for practical field research with socio-educational relevance and intellectual-conceptual approaches. Most of the mentioned research is conducted at UIN Malang, which may be attributed to the program's orientation towards product-based research and its willingness to accept thesis titles based on students' capabilities, unlike other study programs.